Alternatives for recovery, reuse, recycling and final disposal of spent bleaching earth in the vegetable oil refining process (Agroindustria, Sociedad y Ambiente, 2022)
Bleaching earths or clays are raw materials used in the process of refining vegetable oil. Due to its physical conditions, it has characteristics and properties that make it suitable for the adsorption of certain non-glyceride components and impurities, such as carotenoids, chlorophylls, free fatty acids, phospholipids and hydroperoxides, thereby ensuring that the oil meets the necessary requirements to achieve the quality of the final product. The clays can retain between 30-45% of the refined oil and once used in the bleaching process they are disposed in open dumps without any method of recovery. This behavior of consuming and discarding is changing and one begins to see industrial waste as value-added materials that can be used in different processes and thereby promote secondary economies from the properties of waste. In this sense, this publication identifies technological alternatives for the recovery of adhering oil in the clays, regeneration of the qualities of the lands for later use in the refining industry and options for the recovery of the waste for the production of biodiesel and biogas, food supplement for animals, fertilizers, water treatments, aggregates for construction, soap making, among others. Information that was extracted in the database of the Patent Inspiration platform for patent documents and Web of Science for scientific publications, under a search strategy that allowed to identify successful and proven experiences in different countries.
Keywords: Bleaching earth; clays; technology; scientific publications; patents